Duplex ultrasonography predicts safety of radial artery harvest in the presence of an abnormal Allen test. - Abu-Omar, Y; Mussa, S; Anastasiadis, K; Steel, S; Hands, L; Taggart, D (2004)
BACKGROUND: The Allen test is commonly used to assess collateral hand circulation before radial artery harvest for coronary artery bypass grafting. However there is no consensus as to whether an abnormal Allen test is an absolute or relative contraindication to radial artery harvesting. We assessed the safety of harvesting the radial artery using arterial duplex ultrasonography in patients with an abnormal Allen test. METHODS: Two hundred and eighty-seven consecutive patients scheduled for total arterial coronary revascularisation underwent preoperative Allen tests over a 34-month period. Patients with an abnormal Allen test underwent duplex ultrasonography preoperatively to assess the adequacy of the ulnar collateral supply and the suitability of the radial artery for harvesting. RESULTS: Two hundred and forty-four patients (85%) had a normal left Allen test and proceeded directly to radial artery harvest. Forty-three patients (15%) with an abnormal left Allen test underwent duplex ultrasonography scans and of those, 5 patients had an abnormal scan. These patients underwent scanning of the contralateral forearm. Three patients had a normal right forearm arterial duplex scan and the right radial artery was harvested. The mean diameter of the radial and ulnar arteries was not significantly different between the patients with normal and abnormal duplex ultrasonograms. There were no ischemic hand complications in this series. CONCLUSIONS: The Allen test is a quick, easy, and reliable screening test before radial artery harvesting in the majority of patients. Duplex ultrasonography predicts safe radial artery harvest in the majority of patients with an abnormal Allen test.